REKONSTRUKSI PENDIDIKAN KARAKTER DALAM PEMBELAJARAN BAHASA INDONESIA BERBASIS KEARIFAN LOKAL CERITA RAKYAT: KAJIAN ONTOLOGIS, EPISTEMOLOGIS, DAN AKSIOLOGIS - Aria Bayu Setiaji (Lingue : Jurnal Bahasa, Budaya, dan Sastra, 2024)
Abstract This study aims to examine the ontological, epistemological, and axiological dimensions of character education values in Indonesian language learning based on the local wisdom of folklore. The research method used was qualitative with a descriptive approach, focusing on the analysis of the content of folklore and its implementation in learning. Data were obtained through literature review and document analysis, then analyzed in depth to identify the contained character values and their relevance in the educational context. The results show that ontologically, folklore is a cultural reality that contains life values and is part of the community's identity. Epistemologically, character values are acquired through an active, reflective, and contextual learning process. Axiologically, these values are internalized in students' attitudes and behaviors in everyday life. The research findings reveal that the use of folklore can increase learning engagement, critical thinking skills, and strengthen local cultural identity. Furthermore, learning success is influenced by creative and contextual teacher strategies. It is concluded that Indonesian language learning based on folklore is effective in developing language competence while shaping students' character. However, these values need to be studied in depth through a philosophical dimension to understand their nature, meaning, and implications in human life, so that they can provide a strong foundation for implementing learning in schools. Keywords: ontological, epistemological, axiological, character education, folktales